(untitled) (Journal of Medicine, 2011)
Histoplasmosis is an infectious disease caused by the dimorphic fungus Histoplasma capsulatum.. The disseminated form is usually found in immunocompromised patients. A 53 year-old man, renal transplant recipient, was admitted with fever, dyspnea, productive cough, adynamia and weight loss. He was septic, but hemodynamically stable. The tracheal aspirate found intracellular fungi and the peripheral blood exam was compatible with histoplasmosis. The patient presented a progressive worsening of respiratory pattern and needed mechanical ventilation, vasoactive drugs and hemodialysis. A large spectrum antimicrobial therapy was started, including amphotericin B, but the patient died. Keyword: Disseminated histoplasmosis. Kidney transplantation. Immunosuppression DOI: http://dx.doi.org/10.3329/jom.v12i2.7125 JOM 2011; 12(2): 163-165